Relation of IGF-I with subclinical cardiovascular markers including intima-media thickness, left ventricular mass index and NT-proBNP - Eichner, Maximilian; Wallaschofski, Henri; Schminke, Ulf; Völzke, Henry; Dörr, Marcus; Felix, Stephan B; Nauck, Matthias; Friedrich, Nele (Endocrine Connections, 2020)
Several studies revealed relations between low or high insulin-like growth factor I (IGF-I) levels and risk of cardiovascular diseases or mortality, whereas the mechanisms behind these associations are still unknown. The study aimed to explore the relations between IGF-I and changes in surrogate markers of cardiovascular disease including carotid intima-media thickness (IMT), left ventricular mass index (LVMI) and N-terminal pro-brain natriuretic peptide (NT-proBNP). Longitudinal data of the population-based cohort Study of Health in Pomerania (SHIP) were used. IMT was measured by ultrasonography and LVMI was determined based on echocardiography. IGF-I and IGF-binding protein-3 (IGFBP-3) levels were measured by chemiluminescent immunoassays and the IGF-I/IGFBP-3 ratio was calculated. Mixed linear regression models adjusted for known cardiovascular confounders were performed. Statistical analyses demonstrated relations between low baseline IGF-I levels (beta for ΔIMT per s.d. increase -0.044 (s.e. 0.012)) or IGF-I/IGFBP-3 ratio (beta -0.045 (0.012)) and a long-term IMT increase. No associations between IGF-I, IGFBP-3 or IGF-I/IGFBP-3 ratio and changes in LVMI were detected. With respect to NT-proBNP sex-specific associations with IGF-I were found. In women, higher baseline IGF-I levels (beta for ΔNT-proBNP per s.d. increase 5.92 (2.2)) or IGF-I/IGFBP-3 ratio (beta 4.48 (2.2)) were related to an increase in NT-proBNP levels. Among men, U-shaped relations of baseline levels of IGF-I, IGFBP-3 and the IGF-I/IGFBP-3 ratio with an increase in NT-proBNP were found. The study detected significant relations between IGF-I and long-term changes in IMT and NT-proBNP but not LVMI. These findings argue for different effects of the IGF-I axis with respect to various cardiovascular entities.